ADIEU WIKIPEDIA: UNDERSTANDING THE ETHICS OF WIKIPEDIA AFTER GAMERGATE - Famiglietti, Andrew (AoIR Selected Papers of Internet Research, 2015)
This essay explores the possibilities for using the ethical thought of Emmanual Levinas to better understand ethical behavior within the Wikipedia project. At its inception, the free encyclopedia project Wikipedia was hailed by some as an example of a productive method capable of breaking from entrenched systems of power and privilege. However, as the project has matured it has has to deal with the ways these forms of power and privilege have reproduced themselves within its community. In particular, Wikipedia has struggled with a well documented gender gap in its editor base; according to the best estimates available, fewer than 16% of Wikipedia contributors identify as female (Hill and Shaw). Wikipedia’s problematic gender dynamics were further highlighted when, in January 2015, the site’s arbitration committee (or Arbcom) ruled to exclude editors deemed “disruptive” from participating in the article documenting the still-unfolding campaign of anti-feminist harassment dubbed “gamergate.” This action was reported in the press, somewhat inaccurately, as a “feminist purge” of Wikipedia (Hern), largely because of the Arbcom decided to include some high profile Wikipedia editors working to prevent gamergate related harassment in its sanctions. While initial press reports may have over-emphasized the impact of the gamergate arbcom decision, the engagement between Wikipedia and gamergate is still a useful case as it demonstrates how Wikipedia shies away from an understanding of its own ethical guidelines that would foreground the obligation to an embodied other, as found in the work of Levinas. Instead, we see how the project interprets these guidelines in a way that emphasizes procedural fairness and follows Habermas’ prescription for establishing a just discursive environment, as described in previous work (Hansen, Berente, and Lyytinen). This procedural focus may, in part, explain Wikipedia’s continued difficulty in addressing power, privilege and exclusion in its community.